Performance Enhancement of Backward Compatible NGPON2/GPON Systems - Sharma, Dhruva (My University, 2018)
Passive optical networks are getting attention of the researchers because of large number of benefits given by these systems. But, till date, work of the upgradation of conventional PON standards by integrating existing PONs with latest high speed standards are reported very less. More specifically, back compatibility and integration of NGPON2 and GPON is an interesting task for upgrading the existing standard to high bit rates for the fulfilment of ever increasing requirements of end users. It provide the benefits of pay as you grow and also this joint operation of NGPON2 and GPON provides the cost effectiveness and saves the strands of fiber by upgrading the conventional already deployed systems. Time and wavelength division based PON is a groundbreaking technology in the field of access networks and an essential driver for NGPON2 (next generation passive optical network). In this work, a backward compatible integrated TWDM PON and Gigabit PON is demonstrated by incorporating mode division multiplexing. Video overlay is also considered in this work along with back compatibility of PON standards. Cost efficient and reliable system is proposed as required in next generation access networks. Data, audio and video are sent over TWDMPON/GPON and diverse linear polarized modes are analyzed. Proposed system is a new approach for the pay as you grow services. This is a promising integration of two diverse standards that can work on same feeder fiber or ODN without any extra deployment of fiber. Q factor along with BER is evaluated in the system for different link lengths, and different intensity profiles i.e. LP mode profiles. It is evident that TWDM PON is better than GPON and odd LP mode provides better performance in both PON standards. It is observed that NGPON2 performs better than GPON in terms of Q factor and BER. Further analysis of different LP mode profiles in proposed system has been done and it is evident that LP11 mode performs best and LP12 performs worst. Therefore, proposed system is enhanced in performance, cost efficient, uses same ODN, reliable for the future generation networks.
Master of Engineering- ECE
Keywords: Optical communication; Optical networks; NGPON2; GPON